Characteristic time scale of cluster production at the Fermi energy - Pagano, A.; Cardella, G.; De Filippo, E.; Geraci, E.; Gnoffo, B.; Lanzalone, G.; Maiolino, C.; Martorana, N. S.; Pagano, E. V.; Pirrone, S.; Politi, G.; Risitano, F.; et al. (Frontiers in Physics, 2022)
1 The study of Heavy Ion Collisions in the Fermi energy domain (20 MeV/nucleon < E /A < 100 MeV/nucleon) is a fundamental research topic in modern nuclear physics. In the case of semi-peripheral collisions, the Fermi energy regime is characterized by the formation of a transient, neck-like structure that connects a projectile-like fragment (PLF) with a target-like fragment (TLF). The neck structure represents a precursor of the fireball which is a typical overlap of participating nucleons at relativistic energies (E / A> 200 MeV/nucleon). It undergoes an expansion phase in a short time scale of the order of 100 fm/c with the formation of a low density region of nuclear matter; therefore, favoring the clusterisation of intermediate mass fragments (IMF) of atomic number Z (typically) less than 20. Particular emphasis is given to some relevant results obtained by the CHIMERA collaboration in the last decade regarding the time scale of the production mechanisms of the IMFs in neck fragmentation and their neutron enrichment.